(untitled) (HIMALAYA, 2025)
This contribution is an edited version of a wide-ranging conversation between linguistic anthropologist and past co-editor of HIMALAYA, Mark Turin, and Lava Deo Awasthi, the first Chairperson of Nepal’s Language Commission. In the course of the interview, Turin and Awasthi discuss the Commission’s role and establishment, Awasthi’s appointment to the position of Chairperson, his intellectual training and administrative preparation for the task, and the strategic goals and objectives that he brought to the portfolio. The conversation then moves on to a critical reflection of the challenges and achievements of Awasthi’s term as Chairperson, concluding with his vision for mother tongue instruction and linguistic justice in Nepal.